LN

giúp mình câu này với 

thay phép trừ bằng phép cộng với số đối rồi tính kết quả :

a) 3+x=7                      b)(-5)-(9-12) 

 

cảm ơn

VH
13 tháng 7 2024 lúc 20:44

a) `3 + x = 7`

`=>` `x = 7 - 3`

`=>` `x = 4`

b) `(-5) - (9 - 12)`

`=>` `(-5) + (-9 + 12)`

`=>` `(-5) + 3 = -2`

$#haeng2010$

 

Bình luận (0)
PL
13 tháng 7 2024 lúc 20:45

a) \(3+x=7\)

\(x=7-3\)

\(x=7+\left(-3\right)\)

\(x=4\)

b) \(\left(-5\right)-\left(9-12\right)\)

\(=\left(-5\right)-9+12\)

\(=\left(-5\right)+\left(-9\right)+12\)

\(=\left(-14\right)+12=-2\)

Bình luận (0)